Functional Analysis of a Novel CLN5 Mutation Identified in a Patient With Neuronal Ceroid Lipofuscinosis - Luo, Sukun; Bi, Bo; Zhu, Baiqi; Tan, Li; Zhao, Peiwei; Huang, Yufeng; Wu, Gefei; Zhou, Aifeng; He, Xuelian (Frontiers in Genetics, 2020)
Neuronal ceroid lipofuscinoses (NCLs) are a group of autosomal recessive inherited neurodegenerative disorders mainly affecting children, and at least 13 causative genes (CLN1 to CLN8 and CLN10 to CLN14) have been identified. Here, we reported a novel homozygous missense mutation (c.434G > C, p.Arg145Pro) identified in CLN5 gene via whole exome sequencing in a 5-year-old girl. The patient first presented paroxysmal epilepsy associated with vomiting, followed by progressive regression in walking, vision, intelligence and speaking. Combining the molecular and clinical analysis, the diagnosis of NCL could be made, although the missense mutation (c.434G > C, p.Arg145Pro) in CLN5 was evaluated to be a variant of uncertain significance according to American College of Medical Genetics and Genomics (ACMG) standard. We further performed expression and localization studies and our results provide evidence of impaired cellular trafficking of CLN5 to lysosome, indicating that this mutation might be deleterious to the function of CLN5 for its mislocalization. Our study demonstrated the efficacy of next generation sequencing in molecular diagnosis, and a deleterious effect of the variant discovered in our patient on CLN5, triggering the NCL disease.